Human coronary morphology after β radiation brachytherapy of in-stent restenosis. (14th May 2004) - Grewe, P H; Deneke, T; Hanefeld, C; Müller, K-M
Abstract : This case report discusses the human coronary morphological findings 18 hours after brachytherapy (β radiation) of an in-stent restenosis. Brachytherapy produced aseptic inflammation of the periadventitial connective tissue integrating the vasa vasorum in the acute phase. The stent neointima eight months after stenting and acutely 18 hours after radiation consisted of the same cellular components as human stent neointima of specimen not additionally treated with radiation. No evidence of necrosis or excessive fibrotic alterations of the arterial vessel wall have been found.